2016
DOI: 10.1177/1040638716640312
|View full text |Cite
|
Sign up to set email alerts
|

The use of native fluorescence analysis of synovial fluid in the diagnosis of medial compartment disease in medium- and large-breed dogs

Abstract: Abstract. We assumed that proteins are most likely responsible for synovial fluid fluorescence and that changes detected in fluorescence intensity are most likely the result of changes in the concentration of fluorescent proteins. Synchronous fluorescent matrices from synovial fluid samples were measured in the excitation wavelength range of 200-350 nm using a luminescence spectrophotometer. The synchronous matrix of synovial fluid consists of 2 dominant fluorescent centers (F1 and F2) in the ultraviolet regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…The use of urinary fluorescence analysis offers the possibility to detect urinary metabolites potentially associated with the neoplastic process, which could provide a new direction in the current search for predictive and prognostic markers [2,11,19,20]. In our previous studies, we have confirmed the role of fluorescence spectroscopy as a useful diagnostic tool with high-efficiency in ovarian cancer [7] as well as the feasibility of synovial fluid fluorescence fingerprinting to identify disease-specific profiles of synovial fluid metabolites [21].…”
Section: Introductionsupporting
confidence: 54%
“…The use of urinary fluorescence analysis offers the possibility to detect urinary metabolites potentially associated with the neoplastic process, which could provide a new direction in the current search for predictive and prognostic markers [2,11,19,20]. In our previous studies, we have confirmed the role of fluorescence spectroscopy as a useful diagnostic tool with high-efficiency in ovarian cancer [7] as well as the feasibility of synovial fluid fluorescence fingerprinting to identify disease-specific profiles of synovial fluid metabolites [21].…”
Section: Introductionsupporting
confidence: 54%